Evidence of non-extractable florfenicol residues: development and validation of a confirmatory method for total florfenicol content in kidney by UPLC-MS/MS. Issue 6 (2nd June 2016) - Faulkner, Dermot; Cantley, Margaret; Walker, Matthew; Crooks, Steven; Kennedy, David; Elliott, Christopher
ABSTRACT: The parent compound florfenicol (FF) is a broad-spectrum antibacterial compound licensed in the UK for use in cattle, pigs and the aquaculture industry. The analysis of porcine tissues in this study demonstrates that significant amounts of solvent non-extractable FF-related residues are present in incurred tissues (kidney and muscle) from treated animals. The results indicate that methods based on solvent extraction alone may carry a significant risk of reporting false-negative results. The use of a strong acid hydrolysis step prior to solvent extraction of tissue samples is necessary for an accurate estimate of the total tissue FF content. A robust and sensitive method for the determination of total FF residue content in kidney samples by ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) has been developed and validated. This method covers the synthetic amphenicol drug FF and its metabolites, measured as the marker residue florfenicol amine (FFA) as per Commission Regulation (EU) No. 37/2010. Non-extractable and intermediate metabolites are converted to the hydrolysis product FFA, and then partitioned into ethyl acetate. Extracts are solvent exchanged prior to a dispersive solid-phase extraction step, then analysed using an alkaline reverse-phase gradient separation by UPLC-MS/MS. The method was validated around the maximum residue levels (MRLs) set out in Regulation (EU) No. 37/2010 for bovine kidney in accordance with Commission Decision No. 2002/657/EC. The following method performance characteristics were assessed during a single laboratory validation study: selectivity, specificity, sensitivity, linearity, matrix effects, accuracy and precision (decision limit (CCα) and detection capability (CCβ) were determined).